Women Parliamentary Representation in Africa and Growth of Women Businesses - Ngwakwe, Collins; Rachidi, Mamoloko (Acta Universitatis Danubius. Administratio, 2023)
The connection between women representation in parliament and the extent of substantive representation of women’s interest remains ambiguous. Objective: this paper aims to understand if women representation in African parliament catalyses growth in women business ownership in Africa. Prior work: the paper inclines on the normative theory of democracy and the theory of politics of presence through the lens of descriptive or substantive representation. Approach: The paper’s method is both theoretical and quantitative. It uses a cross-sectional secondary data for women in parliament and women ownership of businesses for a sample of 26 African countries, through the application of simple regression analysis. Result: The regression result, which emerges at P>0.05 indicates that within the confines of the 26 African countries used as the sample, women's representations in these African parliaments have not catalysed a significant effect on women’s business ownership in Africa. Implications: The paper provides policy and academic implication as an academic study material in university administration and development classes and for women political manifesto guide. It also provides an agenda for further research. Value: The paper contributes to the political theory of presence by ushering a different result linked to women’s business interests based on an African sample. The paper also contributes a framework and suggests a new concept of inquiry for additional gender equality advocacy, namely the inclusion of women-in-women advocacy for political participation and women’s interest.